The clinical characteristics and treatment of ovarian malignant mesoderm mixed tumor: a systematic review - Xin Wang; Shiyuan Wang; Shujuan Yao; Wei Shi; Ke Ma (BMC, 2022)
Abstract Background Ovarian malignant mesoderm mixed tumor (OMMMT) is a rare clinical entity. To provide reference for the treatment and prognosis of OMMMT, we analyzed the clinical features, pathology and molecular biology characteristic of published cases. Methods The English and Chinese reported cases of OMMMT were selected from PubMed, Clinical Trials.gov and CNKI database from 2000 to December 15th, 2021 following the PRISMA guidelines. Results A total of 63 literatures including 199 OMMMT cases were included. The average age of patients at diagnosis was 56.46 years, the highest incidence age was 60-65 years, and 82% of them were menopausal women. Most patients were diagnosed in FIGO III stage (59.64%). The most common symptom of OMMMT was abdominal pain (60.5%). 61.6% of patients were accompanied by ascites, while ascites was not associated with metastatic tumor and local recurrence. The CA125 of 88.68% patients increased. The most common reported carcinomatous component and sarcomatous component were serous adenocarcinoma (44.96%) and chondrosarcoma (24.81%), respectively. Initial treatment included surgery (94.97%) and taxanes-based (55.10%) or platinum-based (85.71%) chemotherapy regimens. The median survival time of patients was 20 months. Heterologous sarcoma component did not shorten life expectancy. The optimal ovarian tumor cell debulking surgery (OOTCDS), radiotherapy and chemotherapy could significantly prolong the median survival time of patients. Furthermore, platinum drugs could significantly prolong the survival time after comparing various chemotherapy schemes. Besides, the combination of platinum and taxanes was therapeutically superior to the combination of platinum and biological alkylating agents. Conclusion The OOTCDS and platinum-based chemotherapy regimen can improve the prognosis of OMMMT. Targeted therapy might become a new research direction in the future. Since the elderly patients are the majority, the toxicity of new drugs on the elderly patients is more noteworthy.